2013
DOI: 10.5897/ajb12.1506
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical assessment of borehole water used by schools in Greater Giyani Municipality, Mopani district, South Africa

Abstract: In the present study, the physical and chemical quality of several borehole water sources, used by rural schools in Greater Giyani Municipality, were assessed to determine their safety for human consumption. Atomic absorption spectroscopy and ion chromatography were used to determine the chemical quality of water sources. The pH of the water samples varied between 5.29 and 8.3 and tended to be lower in summer and higher in winter. The turbidity values varied between 6.17 and 44.7 NTU in some of the schools. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Most public schools in South Africa are dependent on groundwater due to lack of and/or inadequate municipal water supply. Studies such as [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] have found that groundwater used by school children, mostly in rural areas of developing countries, is of poor quality and has negative health impacts. De Vera [ 1 ] reported that the bacterial count and total coliform in groundwater from deep wells in four selected public elementary schools in the Philippines did not meet the standards, and was required to be treated before drinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most public schools in South Africa are dependent on groundwater due to lack of and/or inadequate municipal water supply. Studies such as [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] have found that groundwater used by school children, mostly in rural areas of developing countries, is of poor quality and has negative health impacts. De Vera [ 1 ] reported that the bacterial count and total coliform in groundwater from deep wells in four selected public elementary schools in the Philippines did not meet the standards, and was required to be treated before drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater used by school children in rural areas in the Giyani region, South Africa had poor microbiological quality, high diversity of pathogenic bacterial organisms ( Salmonella , Shigella , Vibrio species , Campylobacteria , and E. coli ), and high levels of antibiotic resistance by the isolated organisms [ 4 ]. Samie et al [ 5 ] also indicated that groundwater from the schools studied by Samie et al [ 4 ] was not suitable for human consumption based on hardness and high nitrate concentrations, and posed a serious threat to the health of school children. Nitrate concentration in a water sample from the borehole used by the primary school in the Thaba Nchu area in South Africa exceeded the standard by almost tenfold, and was linked to mining-related activities within the vicinity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 ] where Shigella was found to be the least dominant pathogen in groundwater from boreholes. Shigella flexneri is among the most common diarrhoeagenic pathogens in groundwater in the rural districts of the Limpopo Province [ 36 ]. In a study conducted by Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Finding solutions to these problems have been challenged by the current waves in multiple-drug resistance and production of extended spectrum beta-lactamases reportedly demonstrated by enteric bacteria [10]. Antibiotic-resistant genes conferring resistance to a wide variety of antibiotics have been identified in a large range of water environments including drinking water in both developed and developing countries [11,12]. The main risk for public health is that resistance genes are transferred from environmental bacteria to human pathogens.…”
Section: Introductionmentioning
confidence: 99%